Secession and Referendum A new Dimension of International Law on Territorial Changes? - Landi, Giulia (Premio Tesi di Dottorato, 2019)
The book focuses on current developments on territorial changes in International law. The study inquiries about whether according to international law, the referendum is a sufficient or a necessary condition for secession, or both. Through main "cases study", the book finds that there is no sufficient practice and opinio juris to support the existence of an international rule according to which the referendum is a sufficient element to legitimize the birth of a new entity. Nevertheless, there are at least some elements supporting the view that the referendum is becoming a necessary tool in the process for secession, provided that it complies with certain procedural standards.